Fabrication of capacitive micromachined ultrasonic transducers with through-glass-via interconnects - Zhang, Xiao; Yamanery, F. Yalçın; Oralkan, Ömer (Institute of Electrical and Electronics Engineers, 2015)
This paper introduces a novel fabrication method for capacitive micromachined ultrasonic transducer (CMUT) arrays amenable to 3D integration. The work demonstrates that MEMS structures can be directly built on a through-glass-via (TGV) substrate. The key feature of this new approach is the combination of TGV interconnects with a vibrating silicon-plate structure formed by anodic bonding. This method simplifies the overall fabrication process for CMUTs with through-wafer interconnects by eliminating the need for an insulating lining for vias or isolation trenches. Fabrication of CMUTs on a glass substrate and use of copper-filled vias as interconnects can help reduce the parasitic interconnect capacitance and resistance, improving device performance and reliability. This work is especially important for fabricating 2D CMUT arrays and integrating them closely with supporting electronic circuits.
Keywords: 3D Integration; Anodic Bonding; CMUT; Glass; TGV